NWFP Province Pakistan : Procurement Systems Performance Assessment - World Bank (Washington, DC, 2012)
The North West Frontier Province (NWFP) is the third largest province of Pakistan. The developing countries and bilateral and multilateral donors having a concern for increasing the effectiveness, efficiency and transparency of procurement systems, under the auspices of the joint World Bank and OECD Development Assistance Committee (DAC) Procurement Round Table initiative, worked together to develop a set of tools and standards that provide guidance for improvements in procurement systems and the results they produce. Among these tools are included: (i) Benchmarking for the assessment of the structure of the public procurement systems; and (ii) Monitoring and Evaluation of the public procurement systems. With regard to the first deliverable a tool comprising a set of baseline indicators for the assessment of a country system has been developed. This tool comprising four pillars explained through twelve (12) indicators.